ChemInform Abstract: Aza‐Annulation of Enynyl Azides: A New Approach to Substituted Pyridines. Issue 27 (18th June 2015) - Raji Reddy, Chada; Panda, Sujatarani A.; Reddy, Motatipally Damoder
Abstract A novel aza‐annulation of 2‐en‐4‐ynyl azides, derived from MBH‐acetates of acetylenic aldehydes, to synthesized substituted pyridines is developed.